2015
DOI: 10.1111/jfpp.12668
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Blueberries on the Oxidative Stability of Pork Meatloaf During Chilled Storage

Abstract: In the present study, the possibility of using blueberries in order to protect pork meatloaf against oxidation during storage was examined. To this end, the antioxidant effect of blueberries in meatloaf has been investigated by 2,2-diphenyl-1-picrylhydrazyl method and 2-thiobarbituric acid method. During the experiment, meatloaf with normal and lowered content of fat (12.5% of initial fat was replaced with fiber) was tested. The results have shown that the antioxidant activity is higher in the samples with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 39 publications
2
16
0
Order By: Relevance
“…The radical scavenging activity of the spice extracts was evaluated by the DPPH method according to the procedure described by Sánchez-Moreno et al [23] with some modifications. [10] The DPPH • radical scavenging activities of the plant extracts were expressed as Trolox Equivalents Antioxidant Capacity -TEAC (DPPH) values in μM of Trolox equivalent (TE) per g of dry sample. TEAC (DPPH) values were calculated as the ratio of the slope of the linear plot for the scavenging of DPPH • radicals by the extract tested to the slope of the plot for DPPH • radicals scavenging by the antioxidant standardthe water-soluble vitamin E analog Trolox.…”
Section: Antioxidant Properties Of Spice Extractsmentioning
confidence: 99%
See 2 more Smart Citations
“…The radical scavenging activity of the spice extracts was evaluated by the DPPH method according to the procedure described by Sánchez-Moreno et al [23] with some modifications. [10] The DPPH • radical scavenging activities of the plant extracts were expressed as Trolox Equivalents Antioxidant Capacity -TEAC (DPPH) values in μM of Trolox equivalent (TE) per g of dry sample. TEAC (DPPH) values were calculated as the ratio of the slope of the linear plot for the scavenging of DPPH • radicals by the extract tested to the slope of the plot for DPPH • radicals scavenging by the antioxidant standardthe water-soluble vitamin E analog Trolox.…”
Section: Antioxidant Properties Of Spice Extractsmentioning
confidence: 99%
“…[5] The rate of oxidation reaction depends on many factors, like ratio of unsaturated fatty acids to saturated ones, which is strictly correlated with a type of tissue and breed, storage conditions (time and temperature) and/or technological procedures meat is subjected to (mincing, cooking, roasting, etc.). [8][9][10] Chicken meat tends to oxidize more rapidly than pork as it contains a relatively higher content of unsaturated fatty acids. Moreover, minced meat is more prone to oxidation than the whole muscle retail cuts since during grinding the surface of the product increases, which makes it more exposed to ROS.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This results is similar to the inhibition effect of FB in the experiment. Muzolf-Panek et al [7] also suggested that blueberries can protect meatloaf against oxidation during 12 days of storage due to values of bioactive compounds in blueberries, like 2.84 to 3.09 μg/g dry weight resveratrol, which belongs to the group of stilbenes. They also detected 205.4 to 841.3 μg/g dry weight quercetin of flavonols and phenolic acids, such as caffeic, ferulic and p-coumaric acids.…”
Section: Thiobarbituric Acid-reactive Substances Valuesmentioning
confidence: 99%
“…As a result, natural sources are of interest as substitutes to synthetic antioxidants. The application of spices, vegetables, fruit extracts and wine industry residues have received the most attention by consumers and meat processors [7].…”
Section: Introductionmentioning
confidence: 99%